Kajian Etis Normatif dalam Pendidikan Arsitektur di Era Industri 4.0 - Johannes Adiyanto (Universitas Sebelas Maret Surakarta, 2019)
Industry 4.0 is a necessity in the current global era. Indonesia since 2018 has prepared itself with the